(untitled) (Revista da Escola de Guerra Naval, 2023)
Jurgen Brauer and Paul Dunne detect in Military Malthusianism a vulnerability in the occurrence of offsets. This vulnerability is perceived from the fact that the unit cost of large arms systems increases faster than government budget revenues. One of the consequences of this fact is the governments’ search for greater economic efficiency through the globalization of the production and acquisition of arms. If in one hand this theory affirms that we will see more and more unconventional conflicts, on the other it justifies the construction of strategic partnerships in the production of weapons systems, such as the Brazil-Sweden Strategic Partnership, under the FX-2 Program. Thus, this article seeks to evaluate the presence of Military Malthusianism in the Brazilian case, the compliance of the Brazil-Sweden Strategic Partnership with the National Defense Strategy (END, in Portuguese), and analyzes the role of this Partnership in the FX-2 Program.